Uncovering Signatures of DNA Methylation in Ancient Plant Remains From Patterns of Post-mortem DNA Damage - Wagner, Stefanie; Plomion, Christophe; Orlando, Ludovic (Frontiers in Ecology and Evolution, 2020)
The ultra-short DNA molecules still preserved in archeological remains can provide invaluable genetic information about past individuals, species, and communities within the half to 1-million-year time range. The sequence data are, however, generally affected by post-mortem DNA damage and include specific patterns of nucleotide mis-incorporations, which can help data authentication. Recent work in ancient mammals has shown that such patterns can also help assess past levels of DNA methylation in CpG contexts. Despite pioneering work in barley and sorghum, ancient epigenetic marks have received limited attention in plants and it remains unknown whether ancient epigenetic signatures can be retrieved in any of the three main sequence contexts (CG, CHG, and CHH). To address this question, we extended a statistical methylation score originally proposed to trace cytosine methylation in mammal sequence data to accommodate the three methylation contexts common in plants. We applied this score to a range of tissues (wood, cobs, and grains) and species (oak, maize, and barley), spanning both desiccated and waterlogged archeological samples. Ancient sequence data obtained for USER-treated DNA extracts yielded methylation scores on par with DNA methylation levels of modern organellar and nuclear genomes. At the quantitative level, scores were (1) positively correlated to post-mortem cytosine deamination, and (2) replicated relative contributions of CG, CHG, and CHH contexts to DNA methylation assessed by bisulfite DNA sequencing of modern plant tissues. This demonstrates that genuine DNA methylation signatures can be characterized in ancient plant remains, which opens new avenues for investigating the plant evolutionary response to farming, pollution, epidemics, and changing environmental conditions.